Characterization, Biological Activity, and Mechanism of Action of a Plant-Based Novel Antifungal Peptide, Cc-AFP1, Isolated From Carum carvi - Seyedjavadi, Sima Sadat; Khani, Soghra; Goudarzi, Mehdi; Zare-Zardini, Hadi; Shams-Ghahfarokhi, Masoomeh; Jamzivar, Fatemehsadat; Razzaghi-Abyaneh, Mehdi (Frontiers in Cellular and Infection Microbiology, 2021)
Due to the increasing rate of invasive fungal infections and emerging antifungal resistance, development of novel antifungal drugs has been an urgent necessity. Antifungal peptides (AFPs) have recently attracted attention due to their unique ability to evade drug-resistant fungal pathogens. In this study, a novel AFP, Cc-AFP1, with a molecular weight of 3.759 kDa, was isolated from Carum carvi L., purified by ammonium sulfate precipitation and reversed-phase HPLC and finally identified by sequence analysis using Edman degradation. Peptide sequence analysis revealed a fragment of 36 amino acid residues as RVCFRPVAPYLGVGVSGAVRDQIGVKLGSVYKGPRG for Cc-AFP1 with a net charge of +5 and a hydrophobicity ratio of 38%. The antifungal activity of Cc-AFP1 was confirmed against Aspergillus species with MIC values in the range of 8–16 µg/ml. Cc-AFP1 had less than 5% hemolytic activity at 8–16 µg/ml on human red blood cells with no obvious cytotoxicity against the HEK293 cell line. Stability analysis showed that the activity of Cc-AFP1 was maintained at different temperatures (20°C to 80°C) and pH (8 to 10). The results of a propidium iodide uptake and transmission electron microscopy showed that the antifungal activity of Cc-AFP1 could be attributed to alteration in the fungal cell membrane permeability. Taken together, these results indicate that Cc-AFP1 may be an attractive molecule to develop as a novel antifungal agent combating fungal infections cause by Aspergillus species.